Insulin-like growth factor-I induces epithelial to mesenchymal transition via GSK-3β and ZEB2 in the BGC-823 gastric cancer cell line - LI, HEMING (Oncol Lett, 2015)
Metastasis is the most common cause of mortality in patients with gastric cancer. Epithelial-to-mesenchymal transition (EMT), which may be stimulated by insulin-like growth factor-I (IGF-I) is involved in the metastasis of numerous tumors; however, the molecular mechanism by which IGF-I may induce tumor cell EMT remains to be elucidated in gastric cancer. The present study aimed to investigate the induction of EMT in BGC-823 gastric cancer cells. It was identified that IGF-I induced EMT by upregulating the levels of ZEB2 transcription factor, and this was dependent on the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway in these cells. In addition, glycogen synthase kinase 3β (GSK-3β), an intracellular downstream effector of PI3K/Akt, sustained the epithelial phenotype by repressing ZEB2 expression and the subsequent inhibition of EMT induced by IGF-I, suggesting the involvement of a potential PI3K/Akt-GSK-3β-ZEB2 signaling pathway in IGF-I-induced EMT in gastric cancer BGC-823 cells. Overall, the results of the present study suggest that IGF-I induced EMT by the activation of a PI3K/Akt-GSK-3β-ZEB2 signaling pathway in gastric cancer BGC-823 cells. Therefore, this study may provide more useful information regarding the mechanism of gastric cancer metastasis.